2015
DOI: 10.18632/oncotarget.6700
|View full text |Cite
|
Sign up to set email alerts
|

Periostin in tumor microenvironment is associated with poor prognosis and platinum resistance in epithelial ovarian carcinoma

Abstract: The interplay between tumor microenvironment and cancer that causes chemoresistance remains unclear. By analyzing public available microarray datasets, we identified that periostin (POSTN) was overexpressed in cancer stroma in epithelial ovarian cancer (EOC) patients. Immunohistochemistry analysis showed overexpression of stromal POSTN is a powerful independent poor prognostic predictor for EOC patients. Furthermore, patients with high levels of stromal POSTN tend to have higher percentage of cisplatin resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 39 publications
6
84
1
Order By: Relevance
“…However, over 80 ~ 90% patients are diagnosed at the advanced stage, which attributed to the early metastasis and dissemination of the PaC cells [3]. POSTN, originally designated osteoblast-specific factor 2, was found to be overexpressed in various types of human tumors [30, 31], including PaC [1, 32]. POSTN mRNA elevated 42-fold in PaC, and patients with increased expression had a shorter survival tendence [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, over 80 ~ 90% patients are diagnosed at the advanced stage, which attributed to the early metastasis and dissemination of the PaC cells [3]. POSTN, originally designated osteoblast-specific factor 2, was found to be overexpressed in various types of human tumors [30, 31], including PaC [1, 32]. POSTN mRNA elevated 42-fold in PaC, and patients with increased expression had a shorter survival tendence [1].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with recombinant periostin promoted ES-2 cell resistance to both carboplatin and paclitaxel in vitro (Ryner et al 2015). A recent study has shown stromal periostin and not tumour periostin is an independent predictor of OS and DFS in epithelial ovarian cancer (Sung et al 2016). Using the CSIOVDB , POSTN expression was significantly increased in tumour stroma and peritoneal tumours compared with that in primary ovarian tumours.…”
Section: Role Of Periostin In Ovarian Cancermentioning
confidence: 99%
“…For inhibitor treatment in 2D and 3D cultures, 100 nM of rapamycin (Grabiner et al, 2014;Kang et al, 2013;Sarbassov et al, 2006), 250 nM of Torin1 (Cheng et al, 2016;Grabiner et al, 2014;Kang et al, 2013;Thoreen et al, 2012), 10 μM of PF47068671 (Pearce et al, 2010;Schipany et al, 2015;Zhang et al, 2015), 1 μM of MK2206 (Devery et al, 2015;Shen et al, 2015;Sung et al, 2016) and 1 μM of AZD6244 (Devery et al, 2015;Ewald et al, 2015) were employed as these concentrations have been most frequently used in cell-based assays and have a complete effect on their respective targets [ phospho-protein analysis in western blots (see Fig. 4 and western blots in the supporting figures)].…”
Section: Inhibitor Treatmentmentioning
confidence: 99%